1992
DOI: 10.4141/cjas92-048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of index selection for reduced backfat thickness and increased growth rate on sow weight changes through two parities in swine

Abstract: Effect of index selection for reduced backfat thickness and increased growth rate on sow weight changes through two parities in swine McKay, R. M. 1992. Effect of index selection for reduced backfat thickness and increased growth rate on sow weight changes through two parities in swine. Can. J. Anim. . The impact of continued selection for reduced backfat thickness and improved growth rate on weight changes in Yorkshire and Hampshire sows, from breeding as giits to weaning their second litter, was studied.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
1
3
2
Order By: Relevance
“…2, Hampshires tended to produce more live pigs of lighter weight, and there was a significant line-within-breed by diet interaction on live pigs born. Piglet birth weights were not significantly improved by feeding diet 2, and this was in agreement with the findings of Ritchie et al (1960). Feeding increased pyridoxine in sow gestation diets did not significantly influence the 3 wk piglet weight gains in exp.…”
Section: Reproductive Performancesupporting
confidence: 88%
See 2 more Smart Citations
“…2, Hampshires tended to produce more live pigs of lighter weight, and there was a significant line-within-breed by diet interaction on live pigs born. Piglet birth weights were not significantly improved by feeding diet 2, and this was in agreement with the findings of Ritchie et al (1960). Feeding increased pyridoxine in sow gestation diets did not significantly influence the 3 wk piglet weight gains in exp.…”
Section: Reproductive Performancesupporting
confidence: 88%
“…Relatively little information is available on the effect of dietary supplemental pyridoxine on reproduction and nutrient metabolism in sows. Ritchie et al (1960) reported no improvement in litter size of sows fed corn-oat-soybean meal gestation diet supplemented with 11.0 ppm pyridoxine; however, the feeding of supplemental pyridoxine was started in this study from the second month of gestation. Easter et al (1983) reported that gilts fed supplemental pyridoxine at 1.0 ppm to corn-soybean meal diets containing 2.8 ppm available pyridoxine fed from breeding through gestation had increased number of live pigs born (9.7 vs. 8.5, P < 0.05) and weaned (8.7 vs. 7.4, P < 0.07).…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…However, like our study, sow backfat depth at farrowing was less in lines selected for components of lean growth than in control lines (Kerr and Cameron, 1996;Cameron et al, 2002). Unlike our study, weight loss and backfat loss tended to be equal between lines selected for lean growth and control lines (McKay, 1992;Kerr and Cameron, 1996;Cameron et al, 2002). Sow feed intake was less in lines selected for daily feed intake and lean food conversion but greater in lines selected for lean growth rate (Kerr and Cameron, 1996;Cameron et al, 2002).…”
Section: Line Differencescontrasting
confidence: 73%
“…The differences in backfat between the two lines in both experiments were probably due to metabolic differences in partitioning of nutrients for lean and fat tissue deposition (Pettigrew et al 1993). McKay (1992) reported that the body weight loss during lactation was higher in Yorkshire than Hampshire, and higher in select than control line sows which was probably due to a limit-feeding of sows during lactation in that study. Although sow weight gains and backfat retention tended to be superior in Hampshire and select lines of sows fed diet 2, the interactions were not significant.…”
Section: Sow Weight and Backfat Changes During Lactationmentioning
confidence: 96%